URINARY TRACT INFECTION IN PREGNANCY - Lebid, L. (Ukrainian Journal of Nephrology and Dialysis, 2017)
the review contains information about modern conception of the urinary tract infections in pregnant women, the scheme of treatment and prevention of relapse in view of topical diagnosis and category of the teratogenicity of drugs on the criteria of FDA